EVALUATION OF USABILITY OF MAPS OF DIFFERENT SCALES PRESENTED IN AN IN-CAR ROUTE GUIDANCE AND NAVIGATION SYSTEM - Ramos, Ana Paula Marques; Pugliesi, Edmur Azevedo; Oliveira, Renan Furlan De; Tachibana, Vilma Mayumi; Decanini, Mônica Modesta Santos (Universidade Federal do Paraná, 2018)
Abstract Noise from the information communication process produced by the interfaces of navigation systems has overloaded drivers' cognitive processing systems and increased the probability of traffic accidents. This work evaluates the usability of maps of different scales in a prototype route guidance and navigation system. The maps were designed on basic cartographic communication principles, such as perceptive grouping and figure-ground segregation, as well drivers’ requirements for performing a tactical task. Two different scales were adopted, 1:3,000 and 1:6,000, and the maps implemented in the prototype. A total of 52 subjects (26 males and 26 females) participated in an experiment performed in a driving simulator. The maps describe an urban route composed of 13 simple and complex maneuvers. The drivers’ mental workload was measured in terms of visual demand, navigational error and subjective preference. Results reveal that the usability of maps is influenced by map scale variation, and this is related to maneuver complexity. Also, an association between drivers’ visual demand and gender was found, and this was related to drivers’ spatial ability. More implications are presented and discussed.

Resumo Ruídos nos processos de comunicação da informação em interfaces de sistemas de navegação têm sobrecarregado o sistema de processamento cognitivo dos motoristas e aumentado as chances de acidentes de trânsito. Esse trabalho avalia a usabilidade de mapas em diferentes escalas para um protótipo de sistema de navegação e guia de rota em automóvel. Projetou-se mapas de acordo com os princípios da comunicação cartográfica, tal como segregação de figura-fundo e agrupamento perceptivo, bem como na demanda do usuário ao realizar a tarefa tática. Duas escalas foram adotadas, 1:3.000 a 1:6.000, e os mapas implementados no protótipo. Um total de 52 motoristas (26 homens e 26 mulheres) participaram de um experimento em simulador de direção. Os mapas representaram uma rota em área urbana composta por 13 manobras simples e 13 complexas. A carga mental de trabalho dos motoristas foi quantificada em termos de demanda visual, erro navegacional e preferência subjetiva. Os resultados mostram que a usabilidade dos mapas é influenciada pela variação da escala cartográfica, e isto está relacionado a complexidade da manobra. Além disso, a demanda visual está associada ao gênero do motorista, e isto tem relação com a habilidade espacial. Mais implicações são apresentadas e discutidas.
Avaliação da usabilidade de mapas em diferentes escalas apresentadas em um sistema de navegação e guia de rota em automóvel
Keywords: In-car Route Guidance and Navigation System; cartographic design; mental workload; usability; Sistemas de Navegação e Guia de Rota em Automóvel; projeto cartográfico; carga mental de trabalho; usabilidade